2015
DOI: 10.1007/s13277-015-4056-0
|View full text |Cite
|
Sign up to set email alerts
|

piR-55490 inhibits the growth of lung carcinoma by suppressing mTOR signaling

Abstract: Lung carcinoma is the most common human cancer with poor prognosis and has an increasing incidence in recent years. However, the related mechanism of lung cancer onset has not been completely explored. Piwi-interacting RNA (piRNA) is a type of noncoding small RNA with established function in germ cells, and interestingly, piRNA has also been shown to be implicated in cancer biology. In this study, piR-55490 was found to be silenced in lung carcinoma specimens and cell lines, compared with normal lung tissues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 16 publications
1
99
0
Order By: Relevance
“…Recently, piR-55490 was found to be silenced in lung carcinoma specimens and cell lines, compared with normal lung tissues and cells, and piR-55490 suppression led to the gain in the proliferation rate. Further study revealed that piR-55490 suppressed the activation of Akt/mTOR pathway by binding 3’UTR of mTOR messenger RNA (mRNA) and induce its degradation in a mechanism similar to miRNA in lung cancer cells [79]. These results facilitate our understanding of piRNA’s functions and its role in cancer cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, piR-55490 was found to be silenced in lung carcinoma specimens and cell lines, compared with normal lung tissues and cells, and piR-55490 suppression led to the gain in the proliferation rate. Further study revealed that piR-55490 suppressed the activation of Akt/mTOR pathway by binding 3’UTR of mTOR messenger RNA (mRNA) and induce its degradation in a mechanism similar to miRNA in lung cancer cells [79]. These results facilitate our understanding of piRNA’s functions and its role in cancer cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the piRNA–PIWI protein complex in post-transcriptional gene regulation is also slowly garnering attention. Although the exact mechanism remains elusive, investigators initially have reported the sequence specific complementary binding of a piRNA to a target messenger RNA (mRNA) at the 3′ untranslated region (UTR) and subsequent gene regulation, in a manner similar to that of miRNAs [1719]. It is increasingly being recognized that the sequence based complementarity may not be restricted to 3′ UTR and may expand to 5′UTR, the coding sequence or even the introns [20].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, piR-55490 was recently reported to be downregulated in lung cancer patient specimens and to be significantly associated with poor overall survival. Moreover, piR-55490 was shown to function as a potent tumor suppressor by inducing degradation of mTOR mRNA in a miRNA-like manner and thereby suppressing the activation of the Akt/mTOR pathway, leading to inhibition of lung cancer cell proliferation [28]. …”
Section: Introductionmentioning
confidence: 99%